An Analysis of English Video of @carolinakowanz on TikTok - Nurmala; Nehe, Berita; Zambari, Obay (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2024)
In the era of Industrial Revolution 4.0, leveraging technology for language learning, particularly English, has become increasingly vital. Social media, with its wide reach and accessibility, presents a promising avenue for enhancing English language skills. TikTok, a popular social media platform, has emerged as a significant resource for English language learning, particularly among Generation Z. This study delves into the content analysis of English videos on TikTok, focusing on the educational impact of @carolinakowanz's account. The research aims to evaluate the effectiveness of aspect of speaking and their combined impact on user engagement and understanding, especially among Generation Z learners. The study addresses the identified issues such as the prevalence of non-educational content on TikTok, the platform's commercialization, and user boredom in learning. By analyzing @carolinakowanz's content, this research seeks to contribute to the understanding of how TikTok can serve as an effective tool for English language education. Theoretical and practical implications of the study are discussed, emphasizing the role of social media in facilitating language learning, understanding Generation Z preferences in digital education, and providing accessible learning opportunities.